Ball milling as a way to produce magnetic and magnetocaloric materials: a review - Blázquez, JS; Ipus, JJ; Moreno-Ramírez, LM; Álvarez-Gómez, JM; Sánchez-Jiménez, D; Lozano-Pérez, S; Franco, V; Conde, A (Springer, 2017)
Ball milling (BM) is a well-established technique for producing different materials in powder shape. Dynamical analysis of BM helps to optimize the process through simple but general relations (e.g., definition of an equivalent milling time). Concerning the field of study of magnetocaloric effect (MCE), BM is used in different ways: as a single step process (mechanical alloying), as an initial step to enhance mixing of the elements (e.g., to speed up the formation of the desired intermetallic phase) or as a final step (e.g., hydriding of La–Fe–Si). In this contribution, besides a simple description of the effects of some geometrical parameters on the power released during BM and a short review of the BM contribution to the research field of MCE, we will discuss the effect of the microstructure of the starting material and the granular shape inherent to BM on magnetic materials exhibiting MCE.